1993
DOI: 10.1038/361721a0
|View full text |Cite
|
Sign up to set email alerts
|

A sensory role for neuronal growth cone filopodia

Abstract: The dynamic nature of neuronal growth cone filopodia led to the suggestion that the primary function of filopodia is to sample their immediate environment, responding to and transducing environmental signals that affect growth cone behaviour and shape. Filopodia seem well suited to serve as antenna-like sensors, their broad span allows sampling of information over a greatly enhanced radius, and forward-projecting filopodia encounter potential cues in the molecular terrain long before the advancing growth cone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 33 publications
5
119
0
Order By: Relevance
“…Filopodia are finger-like plasma membrane protrusions that are formed upon remodelling of the actin cytoskeleton beneath the plasma membrane 13 . They can be viewed as a sensory organ of the cells that are used to detect and assimilate signals as well as to explore and move into the surrounding microenvironment [14][15][16] . Filopodia are also involved in transporting signalling proteins within tissues over a long range 16 .…”
mentioning
confidence: 99%
“…Filopodia are finger-like plasma membrane protrusions that are formed upon remodelling of the actin cytoskeleton beneath the plasma membrane 13 . They can be viewed as a sensory organ of the cells that are used to detect and assimilate signals as well as to explore and move into the surrounding microenvironment [14][15][16] . Filopodia are also involved in transporting signalling proteins within tissues over a long range 16 .…”
mentioning
confidence: 99%
“…Indeed, the interplay between lamellipodia and filopodia during cell spreading and motility is still controversial. The classical view is that the primary function of filopodia is to sample the immediate environment and to transduce signals that trigger the extension of lamellipodia in a distinct process [14] and [15]. The choice between one and the other mode in actin polymerization would be dependent on the capping protein at the barbed end [16].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble ligands also can cause collapse (Pini, 1993). Since serotonin, a G protein-coupled receptor, exerts this function in other organisms (Haydon et al, 1984;Davenport et al, 1993) and DRG bear 5-HT receptors (Todorovic and Anderson, 1990), we have examined 5-HT as a defined soluble ligand, and found it causes growth cone collapse, which is blocked by 5-HT, receptors. Thus, our interpretation is that GAP-43 serves to amplify a variety of guidance signals from growth cones.…”
Section: G and Growth Cone Collapsementioning
confidence: 99%
“…Peptides augment 5-HT-induced collapse Soluble factors, including neurotransmitters (Davenport et al, 1993), have been identified as important in directing (Kennedy et al, 1994) and retarding neuronal growth (Pini, 1993). In other species, serotonin (5-HT) causes growth cone collapse (Haydon et al, 1984) and downregulation of NCAM-like molecules and fasciculation (Peter et al, 1994).…”
Section: Intracellular Injection Of Peptidesmentioning
confidence: 99%